2017
DOI: 10.1002/jia2.25037
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of timely linkage‐to‐ART within universal test and treat in the HPTN 071 (PopART) trial in Zambia and South Africa: findings from a nested case‐control study

Abstract: IntroductionHPTN 071 (PopART) is a three‐arm community randomized trial in Zambia and South Africa evaluating the impact of a combination HIV prevention package, including universal test and treat (UTT), on HIV incidence. This nested study examined factors associated with timely linkage‐to‐care and ART initiation (TLA) (i.e. within six‐months of referral) in the context of UTT within the intervention communities of the HPTN 071 (PopART) trial.MethodsOf the 7572 individuals identified as persons living with HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 20 publications
1
40
1
1
Order By: Relevance
“…We excluded several studies as they assessed the effect of ART initiation related to CD4 threshold rather than initiating ART soon after HIV diagnosis (Achhra 2017; Danel 2015; Iwuji 2017; Sabapathy 2017; Larmarange 2016; Plazy 2016; Temprano 2015). We further excluded studies that specifically assessed timing of ART in participants who had oppurtunistic infections such as cryptococcal meningitis or tuberculosis meningitis (Bisson 2013; Blanc 2011; Boulware 2014; Degu 2012; Grant 2010; Havlir 2011; Laurelliard 2013; Makadzange 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded several studies as they assessed the effect of ART initiation related to CD4 threshold rather than initiating ART soon after HIV diagnosis (Achhra 2017; Danel 2015; Iwuji 2017; Sabapathy 2017; Larmarange 2016; Plazy 2016; Temprano 2015). We further excluded studies that specifically assessed timing of ART in participants who had oppurtunistic infections such as cryptococcal meningitis or tuberculosis meningitis (Bisson 2013; Blanc 2011; Boulware 2014; Degu 2012; Grant 2010; Havlir 2011; Laurelliard 2013; Makadzange 2010).…”
Section: Resultsmentioning
confidence: 99%
“…They only included PLWH with cryptococcal meningitis.Plazy 2016Wrong intervention. ART initiation was not based on time since diagnosis, but on CD4 count.Sabapathy 2017Wrong intervention. ART initiation was not based on time since diagnosis, but on CD4 count.Temprano 2015Wrong intervention.…”
Section: Characteristics Of Excluded Studies [Ordered By Study Id]mentioning
confidence: 99%
“…Patients diagnosed on the same day as enrolment for HIV care were less likely to initiate treatment in both interventions, possibly related to internalized stigma when receiving an HIV diagnosis .…”
Section: Discussionmentioning
confidence: 98%
“…Patients diagnosed on the same day as enrolment for HIV care were less likely to initiate treatment in both interventions, possibly related to internalized stigma when receiving an HIV diagnosis [37,38]. Data suggested that patients under Treat-All who have had secondary education may be more likely to initiate ART.…”
Section: Findings In Contextmentioning
confidence: 99%
“…The authors appraise the assumptions made by the model and question whether the modelled HBCT programme in western Kenya could be improved [2].As the authors are aware, high prevalence settings often require active outreach to identify a meaningful proportion of the infected population [3]. However, timely linkage to care following diagnosis remains a challenge [4]. Several studies are looking at innovative means of addressing this, including the use of peer navigators [5], mHealth initiatives [6], and same-day ART start [7].Meanwhile, a different -but still valid -question concerns how best to use an existing programme, in this case through repeating it to test more people.…”
mentioning
confidence: 99%